ASSESSING ALTERNATIVES TO ESTIMATE THE STEM VOLUME OF A SEASONAL SEMI-DECIDUOUS FOREST - de Abreu, Jadson Coelho; Soares, Carlos Pedro Boechat; Leite, Helio Garcia (Floresta, 2018)
Abstract The objective of this study was to evaluate the use of linear and hybrid linear models, artificial neural networks (ANN) and support vector machine (SVM) in the estimation of the stem volume in a Seasonal Semi-deciduous Forest. Cubing data of 99 sample-trees of 15 species were used for this purpose. After analysis, we verified that the inclusion of the species as random effect did not contribute to increase the accuracy of the estimates in the structure of a hybrid model. Artificial neural networks and support vector machines, including species as input categorical variables, were the best alternatives to estimate the stem volume of trees of the Seasonal Semi-deciduous Forest. Keywords: Stem volume; artificial neural networks; support vector machines; hybrid linear models; uneven-aged forest. Resumo Avaliando alternativas para estimar o volume do fuste de uma Floresta Estacional Semidecidual. O objetivo desse estudo foi avaliar o uso de modelos lineares e lineares mistos, redes neurais artificiais (RNA) e máquina de vetor de suporte (MVS) na estimação dos volumes dos fustes de árvores em uma Floresta Estacional Semidecidual. Dados de cubagem de 99 árvores-amostra de 15 espécies foram utilizados para esta finalidade. Após análises, verificou-se que a inclusão das espécies como efeito aleatório não contribuiu para aumentar a exatidão das estimativas na estrutura de um modelo misto. As redes neurais artificiais e as máquinas de vetores de suporte, incluindo as espécies como variáveis categóricas de entrada, foram as melhores alternativas para estimar o volume dos fustes das árvores da Floresta Estacional Semidecidual. Palavras-chaves: Volume do fuste; redes neurais artificiais; máquinas de vetor de suporte; modelos lineares mistos; floresta inequiânea.